Design and Implementation of a Microcontroller Based Buck Boost Converter as a Smooth Starter for Permanent Magnet Motor - S. Ravi; Vitaliy Mezhuyev; K. Iyswarya Annapoorani; P. Sukumar (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This proposal proposes a DC/DC Buck Boost converter which has been used as a smooth starter for a DC Permanent Magnet Motor. In the existing system the DC/DC Buck Converter is used which provide the output less than the input Signal. Using buck converter it is difficult to increase the value of the input signal. Hence DC/DC Buck- Boost Converter used from which it is possible to get both the increased and decreased output from the given input. Previously pulse width modulation signals with respective to motor voltage is used. However they produce variations in the voltage and current of the motor. The above problem is overcome by using DC/DC Power converter. The proposed system with reduction in size, reduced ripples and increase in speed makes the system to operate at both low and high power applications. The proposed system results in higher efficiency, reduces the ripple content and the stress. The results are validated through MATLAB/Simulink and real time implementation.